Comprehensive Analysis of Chicken Vessels as Microvascular Anastomosis Training Model - Bo Young Kang; Byung-Joon Jeon; Kyeong-Tae Lee; Goo-Hyun Mun (Archives of Plastic Surgery, 2017)
Background Nonliving chickens are commonly used as a microvascular anastomosis training model. However, previous studies have investigated only a few types of vessel, and no study has compared the characteristics of the various vessels. The present study evaluated the anatomic characteristics of various chicken vessels as a training model. Methods Eight vessels—the brachial artery, basilic vein, radial artery, ulnar artery, ischiatic artery and vein, cranial tibial artery, and common dorsal metatarsal artery—were evaluated in 26 fresh chickens and 30 chicken feet for external diameter (ED) and thicknesses of the tunica adventitia and media. The dissection time from skin incision to application of vessel clamps was also measured. Results The EDs of the vessels varied. The ischiatic vein had the largest ED of 2.69±0.33 mm, followed by the basilic vein (1.88±0.36 mm), ischiatic artery (1.68±0.24 mm), common dorsal metatarsal artery (1.23±0.23 mm), cranial tibial artery (1.18±0.19 mm), brachial artery (1.08±0.15 mm), ulnar artery (0.82±0.13 mm), and radial artery (0.56±0.12 mm), and the order of size was consistent across all subjects. Thicknesses of the tunica adventitia and media were also diverse, ranging from 74.09±19.91 µm to 158.66±40.25 µm (adventitia) and from 31.2±7.13 µm to 154.15±46.48 µm (media), respectively. Mean dissection time was <3 minutes for all vessels. Conclusions Our results suggest that nonliving chickens can provide various vessels with different anatomic characteristics, which can allow trainees the choice of an appropriate microvascular anastomosis training model depending on their purpose and skillfulness.